Systematic HPLC/ESI-High Resolution-qTOF-MS Methodology for Metabolomic Studies in Nonfluorescent Chlorophyll Catabolites Pathway - José Julián Ríos; María Roca; Antonio Pérez-Gálvez (Journal of Analytical Methods in Chemistry)
Characterization of nonfluorescent chlorophyll catabolites (NCCs) and dioxobilane-type nonfluorescent chlorophyll catabolite (DNCC) in peel extracts of ripened lemon fruits (Citrus limon L.) was performed by HPLC/ESI-high resolution-qTOF-MS method. Compounds were identified in samples on the basis of measured accurate mass, isotopic pattern, and characteristic fragmentation profile with an implemented software postprocessing routine. Three NCC structures already identified in other vegetal tissues were present in the lemon fruit peels (Cl-NCC1; Cl-NCC2; Cl-NCC4) while a new structure not defined so far was characterized (Cl-NCC3). This catabolite exhibits an exceptional arrangement of the peripheral substituents, allowing concluding that the preferences for the NCC modifications could be a species-related matter.